Resistance to Ceftriaxone and Azithromycin in Neisseria gonorrhoeae Isolates From 7 Countries of South America and the Caribbean: 2010-2011 - Thakur, Sidharath Dev (2017)
Fil: Thakur, Sidharath Dev. Department of Microbiology, College of Medicine; Estados Unidos.